Pengembangan tanda baca aksara Lontara - Abd Aziz Ahmad; Pangeran Paita Yunus; Ali Ahmad Muhdy (Seminar Nasional LP2M UNM, 2019)
This study aims to develop punctuation in Aksara Lontara. The addition of consonants has long been a heated debate between those who want to add punctuation to dead letters and those who refuse. They refused on the grounds that they wanted to preserve the culture as the original script. While those who want to develop on the grounds that everything can be developed to adjust the development of the times. It is also recalling that various script in this world experiencing development for example Latin and Arabic script. This research was carried out through Research and Development procedures, with field trials. The main objective of this study is to develop textbooks that contain writing techniques for Aksara Lontara, and the development of punctuation used as symbols of consonants. The data collection was carried out by distributing questionnaires and conducting in-depth interviews with respondents including material experts, media experts and observers of the Aksara Lontara. The results of the study showed 89% of the respondents stated their agreement to develop the Aksara Lontara. Based on the results of the study, the researchers set a small "MA" letter is placed on the script as one of the development of punctuation, for example a small "MA" letter placed above "RA" will say "r". As a product, this study produces a standard about the process and practical steps for writing the Aksara Lontara.